Tinjauan Hukum Islam Terhadap Ritual Lewak Tapo Di Desa Weranggere Kec. Witihama Kab.Flores Timur - Jakaria M. Sali; Iskandar; Aini Aprilariesta Hanggarani; Marwan Gazali (Muhammadiyah University of Surabaya, 2025)
This study is entitled